Um estudo fenomenológico sobre a resiliência em produções textuais de alunos do atendimento educacional especializado - Pereira, Priscilla Alves (2024)
The aim of this dissertation is to observe, describe and understand a phenomenology of resilience in the literary productions of students in the 6th year of elementary school – final years. The guiding question was: how is the resilience of students in specialized educational care in the 6th year of elementary school revealed, expressed in their literary productions? In this context, over the course of two months, observations, dialogues, and text production took place with three students from this grade who are part of the Special Education Center at the chosen school. About the theoretical basis, the concepts of existential involvement and reflective detachment by Yolanda Cintrão Forghieri (2002), empathic understanding by Carl Rogers (1997) and resilience as psychological flexibility by Vitor Gomes (2015) were adopted. Existential phenomenology to promote an approach that explores the basic meanings of students' existence and experiences constitutes the research methodology. Textual productions, non-directive interviews and field diaries were analyzed as tools for understanding the phenomenon. In addition to the dissertation, the result was the production of five video lessons on resilience and special education for researchers and teachers, which will be available on the channel of the Phenomenology in Education Research Group. In short, we hope to integrate the insights that emerge from the research into the context of experiences to strengthen students' resilience to foster a more inclusive and supportive environment